Earthquake And Landslide Disaster Risk Assessment At The University Of Defense: A Preliminary Study - Say Marina Octavia; Adi Subiyanto; Deffi Ayu Puspito Sari; Pujo Widodo; Admiral Musa Julius Sipahutar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The geographical location of the University of Defense in Bogor Regency, Citereup Sub-district, Bogor, West Java, is a sloping terrain that can potentially cause landslides. The InaRISK map released by BNPB, shows that the Defense University is located in an area of Bogor Regency that is prone to disasters, especially landslides. Disaster risk assessment is an approach to show the potential negative impacts that may arise due to a potential disaster. The potential negative impacts are calculated based on the level of vulnerability and capacity of the area. This potential negative impact is seen from the potential number of people exposed, property loss, and environmental damage (PERKA BNPB, 2012). Researchers conducted an analysis of landslide and earthquake disaster vulnerability at the University of Defense. A study of building and population vulnerability to potential earthquakes and landslides was conducted at the University of Defense. The components of social vulnerability at the University of Defense in the event of an earthquake and landslide were obtained. Researchers obtained data on population capacity and building conditions at the University of Defense. Landslide and earthquake disaster risks have the potential to occur at the University of Defense. The University of Defense has the potential threat of landslides because the buildings of the University of Defense are located on hilly slopes. The vulnerability of the University of Defense buildings, the University of Defense buildings have not been designed to be entirely earthquake resistant. This can be seen in some buildings that have visible cracks. It is necessary to retrofit or strengthen the foundations of buildings in the Defense University area that have experienced a decrease in performance such as cracking, shifting, displacement. An important component where the University community and students need self-protection and rescue skills through training.